Gardnerella vaginalis-associated bacterial vaginosis in Bulgarian women - Gergova,Raina T. (2013)
ABSTRACT BACKGROUND: Bacterial vaginosis (BV) is the most common cause of vaginal discharge in women of reproductive age. The purpose of this study was to determine the frequency of BV in Bulgarian pregnant and nonpregnant women from several age ranges and to compare three different laboratory methods for Gardnerella vaginalis detection in patents suffering from BV. METHODS: Between September 2011 and June 2012, 809 women of 16-40 years of age separated in two major groups: nonpregnant - 469 (355 with and 114 without symptoms) and pregnant - 340 (213 and 127 respectively) were enrolled for the study. The women underwent three different laboratory tests simultaneously: scoring of Gram staining of vaginal smear, culture, and polymerase chain reaction (PCR) assay for G. vaginalis. RESULTS: The microscopic method detected high frequency of BV in symptomatic (57%) whereas only a minority of asymptomatic subjects (14%) were detected. G. vaginalisassociated BV was diagnosed in approximately equal proportions when evaluated with PCR and microscopic method for both pregnant and nonpregnant women. The comparative analysis of microscopic evaluation, culture and PCR assays demonstrated greater concurrence (about 90%) between Gram staining and PCR detection for BV, than both methods compared to culture. The combination of microscopy and PCR turned out to be very reliable and repeatable for detecting G. vaginalis-associated BV. CONCLUSIONS: This is the first comparative investigation on the epidemiology of G. vaginalisassociated BV in Bulgaria. The established highest frequency in the young Bulgarian women (21-30 years) is alarming and should be considered in prophylaxis and reproductive programmes.